DIVERSIFIKASI ICE CREAM IKAN BANDENG SEBAGAI PENINGKATAN PENDAPATAN IRT DI DESA TASIWALIE, KECAMATAN SUPPA - Fitri Indah Yani; Andi Adam Malik; Sahabuddin Sahabuddin; Rismawaty Rusdi; Nurul Mutmainnah; Ummu Kaltsum; Yusdalifa Ekayanti Yunus; Yushra Yushra; Muh. Iqbal Quraisyin (Jurnal Abdi Insani, 2023)
Tasiwalie Village is one of the coastal villages located in Suppa districtc which is named Lowita Beach. This beach has been very crowded since 2015, both local and foreign visitors. However, all activities on the beach stopped due to Covid-19 in 2019. PKM activity was carried out to diversify milkfish ice cream as an increase in income for housewives (IRT) in Tasiwalie village, Suppa district. The purpose of this activity is to provide training to IRTs in opening up insight into home industry entrepreneurship through processed milkfish products into milkfish ice cream. Implementation of activities October 29, 2022. The method of implementation includes socialization which aims to provide an overview of the benefits of fish consumption and various ways of processing fishery products. The PKM team itself provided tools and materials for activities by empowering milkfish from ponds in Tasiwalie village itself. Furthermore, we provide training in the form of hands-on practice on how to make milkfish ice cream. As a result of this PKM activity, the IRT and local residents know the benefits of consuming fish and various processed fishery products. During the practice process, it went well and the IRTs easily understood the ingredients and steps in the process of making milkfish ice cream. The practice results are packed with a quantity of 80 cups of ice cream. An IRT can start a business from the IRT itself or submit a proposal for village assistance. This activity can hone the spirit of creativity in entrepreneurship to increase household income. It can be the first step in cultivating a new spirit after the Covid-19 pandemic.